Lexical Metaphors and Cultural Defense: How Karo Youths Preserve Tradition through 'Minyak Pengalun' - Tarigan, Karisma Erikson (Talenta Publisher, 2025)
The aim of this study is to explore the role of lexical metaphors in the preservation of cultural heritage among Karo youths, focusing on the traditional practice of using